Pengaruh Produk Harga Promosi Dan Pelayanan Terhadap Minat Beli Konsumen Pada Toko RP Shop Di Metro - Septiana, Septiana; Baskoro, Ery (Jurnal Manajemen DIVERSIFIKASI, 2021)
The more choice of stores there are, there are many things that consumers should consider in choosing to shop at a trusted store. Currently, most consumers change their mindset in using a product. Someone in spending money often prioritizes wants over needs. The purpose of this study was to determine the effect of products, prices, promotions and services on consumer buying interest in Rp Shop in Metro. This type of quantitative research is numerical and qualitative data is material. Data collection techniques were by conducting library research and field with survey techniques and using questionnaires. Sampling using accidental sampling technique obtained 80 respondents. Data analysis used Statistical Product and Service Solutions (SPSS Version 20). The results of the discussion were that the Product tscore = 0.281 ttable = 1.665, Price tscore = 2.562 > ttable = 1.665, Promotion tscore = 2.831, > ttable = 1.665 and Service tscore = 2.313 > Ttabel = 1,665 . The results of the discussion that has been done show that the product has no effect on consumer buying interest. Meanwhile, prices, promotions and services have a positive and significant effect on consumer buying interest. The F test shows that the value of Fscore = 3.321> Ftable value of 3.117, it can be concluded that product, price, promotion and service variables together have an influence on buying interest, thus Rp Shop must still pay attention to products, prices, promotions and services to increase consumer buying interest.